STRATEGI PENINGKATAN KUALITAS PELAYANAN KEPARIWISATAAN DALAM UPAYA MENINGKATKAN JUMLAH WISATAWAN NUSANTARA DAN MANCANEGARA DI KOTA PALEMBANG - Edwar Juliartha (Publikasi Penelitian Terapan dan Kebijakan, 2020)
Review of the national constellation of tourism at this time could not be denied. that policy development in the field of tourism, particularly the development of local tourism sector remains a critical issue in the implementation of national development. In the report OECD Tourism Policy and International (1987) stated that, the success in the development of tourism will provide a positive impact on the three main things, namely "the National stimulation of economic growth, the maximization of exchange foreigner, and the creation of jobs”. Many of the opportunities and challenges also need to be faced with serious, because in the current era of regional autonomy, the district / city attempted exploit tourism sector as a superior program. Government of South Sumatra Province has undertaken efforts in the various regional regulations, which came up with the sting Department Strategic Plan to promote tourism in the city of Palembang is a reference guide for the whole apparatus of Culture and Tourism Department of Jakarta, with lnstasi related agencies, stakeholders and other people so that the similarity of views. Description is a basic program that describes the development of tourism in the city of Palembang is basically in order to increase the role of tourism in supporting the regional economy and increase the increase the welfare of the people. Thus, the Local Government through the Department of Palembang City Culture and Tourism, can coordinate to the companies included in the tour industry by conducting various activities such as promotions, marketing of tourism through various programs. Kotler and Fox (see Yoeti, 2002: 1) the formulation of a strategy must be based on and be guided to: Environment analysis, Resource Analysis and Formulation Steps Goals. In formulating a strategy tourist destination, it is recommended done through three levels, namely: First, Doing the analysis on the group of companies that are the tourist industry in the tourist destination is. Second, it related to the strategic policies of regional governments on the development of tourism. Third, the strategy of tourism development in the regional accessibility, facilities, objects and attractions, and other supporting facilities.